Non linear analysis of heart rate variability in HIV/AIDS infections (Research, Society and Development, 2022)
The availability of Antiretroviral Therapy (ART) resulted in a drastic reduction of morbidity and mortality associated with the human immunodeficiency virus (HIV). However, the therapy has a series of adverse effects, including autonomic dysfunction. The analysis of HRV allows the evaluation of the sympathetic and parasympathetic involvement in the cardiac neuromodulation. Given the above, the objetives were: to verify whether HIV infections produce changes in cardiac autonomic modulation; to identify whether the cardiac autonomic modulation of the HIV-infected population is sensitive to respiratory sinus arrhythmia (RSA); and to investigate whether time to diagnosis of HIV infection influences HRV. A total of 49 individuals with HIV/AIDS and 21 healthy individuals were assessed. HRV measurements were taken for 20 minutes in the supine position, using the heart rate monitor Polar RS810CX, followed by the RSA maneuver. In both conditions, the RR intervals, typical of HRV, were analyzed by linear and nonlinear indices. Only two nonlinear indices, i.e., %REC and Shannon Entropy, showed statistically significant difference (p=0.004), when comparing both HIV/AIDS and control groups, indicating reduced HRV in the HIV/AIDS group. It is suggested that the RSA maneuver, in turn, improved the autonomic modulation, because the reduction of %REC after the maneuver indicates increase in the parasympathetic modulation. In this way, it is concluded that the HIV/AIDS group showed decreased HRV in the nonlinear analysis; and increased vagal modulation was observed during the ART maneuver. The time to diagnosis has shown to have no influence on HRV.